Evaluation of the business environment quality through the perception of business as part of the ongoing reform of the state supervisory oversight reform - I. V. Vyakina (Модернизация, инновация, развитие, 2019)
Purpose: the current research aims to study the influence of the subjective perception of control and supervisory activities by regional business on the business environment quality as part of the ongoing state control and supervisory activities reform. The article has solved the following tasks: key factors determining the quality of the business environment and the perception by entrepreneurs of the state economic policy have determined; entrepreneurs' perception of the state activity in reforming state control (supervision) in the Tver region has assessed; main problems arising during the implementation of state control (supervision) measures have identified ); ways have proposed t for their elimination.Methods: study based on systematization and analysis of the results of sociological polls to assess the impact of state and municipal control (supervision) on business, which conducted in Tver region for three years (from 2016 to 2018) and covered more than three hundred heads of small, medium and large enterprises of all municipalities of the region. Content analysis of the regulatory framework and economic and statistical evaluation of the results of sociological surveys carried out; tabular and graphical data visualization methods applied.Results: despite the implementation of the reform and the reduction in the number of inspections in Tver region, an analysis of the results of a survey of entrepreneurs indicates a contradictory situation in the administrative conditions of the business environment. There is no reduction in the administrative burden on business in the subjective perception of entrepreneurs. At the same time, the firm orientation of inspectors for the collection of fines and the fiscal orientation of inspections remains.Conclusions and Relevance: conceptual approach to the implementation of the ongoing reform of state control and supervision activities involves the identification and elimination of administrative barriers with the active participation of the business community. Entrepreneurs do not feel the reduction of administrative burden on business according to their subjective perception. The perception of control and supervisory measures by business representatives determines the quality of the business environment, which has a significant impact on the motivation and performance of business entities. There is no change in the fundamental model for the implementation of state control and supervisory activities according to the business community.